'Family is My Diabetes Savior': A Case Study of Family Support in Reaching Goals of Self Care Adherence in Diabetic Patient - Rahmah, Gabby Novikadarti; Sukartini, Titin; Utami, Sri (International Journal of Nursing and Health Services (IJNHS), 2023)
Background Family as the closest person for Diabetic patients has had an important role in providing good care for a patient. Those with diabetes and their family assume the bulk of the responsibility for day-to-day management. Therefore, it is important to assess and explore the perception of family support to succeed in Diabetes Mellitus self-care adherence. Objective: The objective of this study was to explore the meaning of family support in self-care adherence of patients with Diabetes Mellitus. Method: This study applied a descriptive qualitative by-case study approach. The data were collected through in-depth interviews. There were fifteen persons with diabetes mellitus as participants. Data consisted of in-depth interview recordings and field notes. Data were transcribed and analyzed using Colaizzi’s method. Result: Four themes emerged including emotional support, reward support, instrumental support, and informational support. Conclusion: Family support is crucial for managing Diabetes Mellitus. It is often overlooked when designing behavioral interventions for type 2 diabetes mellitus. Conclusion: The results obtained from this study can be essential information for nurses to formulate further family-based interventions to increase adherence to self-care in patients with Diabetes Mellitus. Recommendation: Recommendation: It is important for a nurse to give standardized information based on the development of knowledge and practice about Diabetes Mellitus. Future studies about the content of health information for a patient with Diabetes Mellitus is needed